PARABOLIC TROUGH COLLECTOR CONCENTRATING SOLAR POWER AS STEAM PRODUCER USING SOLAR IRRADIATION OF CEPU, BLORA, CENTRAL JAVA - Andrian Aziz Burhan A.S; Dzul Fadhli Aziz; Muhammad Nur Hidayat (Scientific Contributions Oil and Gas, 2018)
Alternative energy sources has grown lately, especially for solar energy harnessed with Concentrating Solar Power (CSP) to produce steam that will be converted into a certain form of energy. The steam produced can also be used for petroleum industry to reduce the fuel usage in boilers. Daily solar irradiation of 5.18001 – 5.21909 kWh/m2 received by Cepu, Blora, Central Java, is deemed sufficient for CSP with parabolic trough collector (PTC) as steam producer. This paper describes the designing of the parabolic trough collector CSP, temperature increase gained from PTC, and peak temperature gained from 1 PTC. The initial experiment of PTC in cloudy, sunny, and cloudy-sunny-cloudy weather resulting in water temperature increase gained to be 172oC, 401.1oC, 285.9oC using Cepu District solar irradiation. Further experiments will be done to find out the relationship between temperature over time.